Structural characterization and fire performance of geopolymer-glass fiber composite panels - Ye, Kai (2023)
With a specific emphasis on understanding the thermal and fire resistance, in this work, sodium- and potassium-type metakaolin geopolymers (with Si:Al > 2) reinforced with glass fiber (GF) fabrics were manufactured. X-ray diffraction and solid-state nuclear magnetic resonance spectroscopy were used to understand the changes in structure and evolution of phases with temperature. The geopolymer matrices have shown stability up to 700 °C, above which a fiber–matrix interaction was detected before they crystallized into different phases at 1000 °C. The fire resistance times of these panels (12–17 mm thick) when a temperature profile similar to ISO 834 fire curve was imposed were 53.6–55.1 min for Na-GF and 53.2–68.7 min for K-GF composites. Further, one-dimensional thermal analysis using cone calorimeter has suggested the initiation of cracking through the matrix during dehydration because of stress relief. This had an influence on the fire resistance timing of the panels. Despite this, both composites still retained ∼25–30% of their initial flexural strength after the furnace test, which was understood as a compromise between the variations of formed phases and morphological features in the exposed and unexposed sides.